PRÓPOLIS OBTIDA POR HIDROLISE ALCALINA E AÇÃO SOBRE Staphylococcus aureus - ANDRADE, U.; HARTMANN, W.; FUNAYAMA, S.; ALENCAR, S. M.; MASSON, M. L. (Ars Veterinaria, 2010)
The Brazilian propolis is investigated for its antibacterial properties. The aim of this work was to establish the extraction and purification method to display the antibacterial activity. Propolis of Apis mellifera was obtained from bee hives cultivated in Parana State, Brazil. In this study, we used ATCC 25923 Staphylococcus aureus strains and 158 Staphylococcus aureus strains isolated from cows with clinical mastitis. Extraction and partial purification: Several fractions were obtained during the partial purification: a crude ethanolic extract of propolis, a resinous material in ethanolic solution and an alkaline hydrolysis water-soluble compounds solution. The results show that the alkaline hydrolysis water-soluble compounds solution had a minimal inhibitory concentration of approximately 155.46 g/mL for Staphylococcus aureus. In this work, we obtained an aqueous solution of organic compounds extracted from Apis mellifera propolis that bears physical-chemical and biological characteristics capable to inhibit the proliferation of Gram-positive bacteria. KEY-WORDS: Propolis; Apis mellifera; Antibacterial activity; Alkaline hydrolysis.